Cancer-associated IDH2 mutants drive an acute myeloid leukemia that is susceptible to Brd4 inhibition - Chong Chen; Yu Liu; Chao Lü; Justin R. Cross; John P. Morris; Aditya Shroff; Patrick S. Ward; James E. Bradner; Craig B. Thompson; Scott W. Lowe (2013)
Somatic mutations in the isocitrate dehydrogenase (IDH) genes IDH1 and IDH2 occur frequently in acute myeloid leukemia (AML) and other cancers. These genes encode neomorphic proteins that produce the presumed oncometabolite 2-hydroxyglutarate (2-HG). Despite the prospect of treating AML and other cancers by targeting IDH mutant proteins, it remains unclear how these mutants affect tumor development and maintenance in vivo, and no cancer models exist to study the action of IDH2 mutants in vivo. We show that IDH2 mutants can cooperate with oncogenic Flt3 or Nras alleles to drive leukemia in mice by impairing the differentiation of cells of the myeloid lineage. Pharmacologic or genetic inhibition of IDH2 triggers the differentiation and death of AML cells, albeit only with prolonged IDH2 inhibition. In contrast, inhibition of the bromodomain-containing protein Brd4 triggers rapid differentiation and death of IDH2 mutant AML. Our results establish a critical role for mutant IDH2 in leukemogenesis and tumor maintenance and identify an IDH-independent strategy to target these cancers therapeutically.